Relação da força muscular de membros superiores e inferiores e índices de gravidade na doença pulmonar obstrutiva crônica - Marino, Diego Marmorato (2009)
Introduction: Individuals with chronic obstructive pulmonary disease (COPD) present a decrease in peripheral muscle strength, leading to impaired mobility and increased death risk. However, there are a lack of studies that verify if the peripheral muscle strength have relationship with the BODE index scale and fat-free mass. Objectives: To verify the relationship between maximum upper-limb (UL) muscle strength and lower-limb (LL) muscle strength with a BODE index, isolated variables and fat-free mass in subjects with moderate to very severe COPD. Methods: Twenty-six individuals with moderate to very severe COPD (FEV1<80% of predict) were evaluated regarding body composition (body mass index-BMI and fat-free mass), BODE index, handgrip force (HGF) and one repetition maximum test (1RM) of the UL and LL. Results: Observed moderate to strong positive correlation (Pearson, p <0.05) between peripheral muscle strength with the fat-free mass and distance walked in the six-minute walk test (6MWD). However, the BODE index were not correlated with force measurement or fat-free mass. Conclusion: It can be concluded that the evaluation of peripheral muscle strength is not related to the BODE index. In such case, the peripheral muscle force measures need be used assisting the assessment of COPD subjects performance.